Análisis de la oferta y la demanda del almacenamiento de maiz duro para el proyecto Pacalori - Chalán Gualán, Luis Daniel (2015)
In Ecuador, the growing demand for corn for human consumption and for the feed industry, reveals the need to handle the grain post-harvest. Small and medium farmers do not have adequate infrastructure in the areas of production. In these considerations, in the "Plan of use and control of water in the province of Los Rios-PACALORI" work "Analysis of supply and demand hard corn storage for PACALORI project" was held, whose objectives were: to diagnose existing collection centers in the transfer Calabi-Lechugal-Puebloviejo; determine the current and potential annual corn, supervised by classifying LIDAR aerial orthophotos, by implementing a proposal from maize which allowed maximize the income of producers, optimization and design of water resources and infrastructure size macro level necessary to store corn. The infrastructure is located strategically, considering the road, where two collection centers were chosen taking into account the existing operating associatively and as a result of reconciling efficiency targets to achieve maximum spatial coverage and equity of corn producing areas.